Personality traits and investment intention: the moderating effect of financial literacy - Gopal Khanal; Prof. Dr. Tara Prasad Upadhyaya (HM Journals, 2025)
Purpose: The study aims to investigate that personality traits have a significant effect on investment intentions with the moderating role of financial literacy of MBA and MBS students of TU-affiliated colleges in Butwal. Methodology: A stratified sampling technique was used, targeting 247 MBA and MBS students of TU-affiliated colleges situated in Butwal out of a total population of 625. An adopted questionnaire with a seven-point Likert scale is used with a descriptive and causal comparative research design, complemented by a comprehensive array of statistical measures, descriptive statistics, correlation, and regression. These are chosen for robust data analysis with Smart PLS student version and IBM SPSS Statistics version 20. Key Findings: The findings of the study are that there is a significant effect of personality traits (conscientiousness & openness to experience) on investment intention, but neuroticism, extraversion and agreeableness do not have a significant effect. Additionally, financial literacy has a moderating role between the personality traits and investment intentions. Moreover, the financial literacy shows the negative correlation with investment intention. Implications: The implications of the study help in financial advising and decision-making, financial literacy programs, policy makers and individual investment decisions to make the fruitful investment.